The process of patient education in nursing practice: PROCES EDUKACIJE PACIJENATA - PAVLOVIĆ, JELENA P; Đukić, Ivana (PONS - medicinski časopis, 2025)
Introduction. Due to the long duration of the disease, patients are faced with limited health resources, shorter hospitalizations, so they are forced to stay and carry out the treatment for the disease independently or with the help of other persons outside the health institutions. All this emphasizes the trend and the need to encourage a healthy lifestyle and train patients to take care of their own health. The aim of this review was to describe the process of patient education. Two aspects of health education are distinguished: content (what is learned) and process (how the material is learned). Education affects the behavior of patients, which changes knowledge, skills and attitudes, which is necessary in order to preserve and improve one's own health. The patient education process includes several steps: assessment of educational needs, setting educational goals, defining content, activities and learning aids (learning plan), conducting education and evaluating what has been learned. It is important to harmonize educational strategies with the patient's age, because there is a different approach to children, elderly people, people with special needs, etc. Educational activities in health care include three interrelated domains: cognitive (related to the acquisition of certain contents); affective (implies change of attitudes and development of abilities) and psychomotor (refers to the development of practical skills). A key component of the education process is the assessment of patient needs related to the area of ​​education. A nurse must be adequately qualified to assess educational needs, as this is a prerequisite for successful education. In Bosnia and Herzegovina, patient education is not carried out regularly and completely.Conclusion. Patient education has always been an integral part of the work of nurses, and in today's circumstances, the need for it is increasing. Graduated nurses are the main and responsible bearers of educational interventions.Keywords: education, patients, nurses, chronic diseases.
Keywords: Education; patients; chronic disease; nurses